Taxation and competitiveness of the Greek travel agencies - Diakomihalis, Mihail N; Mougios, Nikolaos; Diakomichalis, Nikolaos-Marios N (Archives of Business Research, 2019)
The purpose of this study is to investigate the impact of the tax burden on the travel agencies in Greece as compared to the corresponding effect of taxes on the travel agencies of the competitive countries, Spain, Italy, Croatia, Malta, Cyprus and Turkey. The aim of this paper is to reveal the impact of taxation on the tourism sector of Greece in relation to the travel agencies of the competitive countries. A primary research was conducted in the travel agencies of Athens metropolitan city. The results of the research showed that the gross sales increases with a decreasing trend in the years 2014–2016. Furthermore, package tours sales are falling with the highest decrease being recorded in external package tour sales (-6.17 %). The sales of internal package tours record a decrease of 1.44 %. The Greek travel agencies believe they have financial losses and competitiveness decline because of the increase in income tax and Value Added Tax (VAT). They consider that have experienced a fall of approximately -53.33 % in gross sales, as a results of losses from Cyprus, Turkey and Spain. However, the Greek travel agencies appreciate that the level of their competitiveness (based on the differences in income tax and VAT rates) is the lowest in relation to the aforementioned competitor countries, assessing the most competitive travel agencies to be those of Cyprus, Turkey, Spain, Croatia, Italy and Malta. The limitations of this work include the issue of fiscal policy which focuses on and explores the main taxation of income and VAT and their rates, ignoring other “secondary” taxes, fines, etc.